Drone for a Cleaner Coast: Monitoring and Analysis of Marine Debris at Sindulang Beach - Kumaat, Joyce; Batee, Grace Ezlin (Jurnal Ilmiah Platax, 2023)
This research aims to evaluate the capabilities of the DJI Phantom 4 Pro unmanned aerial vehicle (UAV) in monitoring the accumulation points and analyzing the characteristics of marine debris stranded at Sindulang Beach. The research methodology employed a descriptive approach with a survey method, including data collection through observation, documentation, and direct field surveys. Aerial photos were obtained from the drone, along with ground photography using a GPS map camera and the drone itself. Data analysis was conducted using Agisoft Metashape Professional and ArcGIS 10.8 software to map the distribution of marine debris accumulation points. The drone monitoring results allowed us to describe the characteristics and variations in types of marine debris, with plastic waste dominating, followed by glass, rubber, and fabric debris. The DJI Phantom 4 Pro unmanned aerial vehicle produced high-resolution aerial photos, enabling the identification of the distribution of marine debris accumulation points at Sindulang Beach and the creation of distribution maps along the Sindulang coastal area. The mapping results provide valuable information about the distribution of debris on Sindulang Beach. Based on the monitoring results using the unmanned aerial vehicle (UAV) or drone, it was found that approximately 80% of the intertidal area at Sindulang Beach was covered by debris, indicating a significant level of pollution. Keywords: Marine Debris, Unmanned Aerial Vehicle, Sindulang Abstrak Penelitian ini bertujuan untuk mengevaluasi kemampuan pesawat tanpa awak DJI Phantom 4 Pro dalam pemantauan titik kumpul sebaran marine debris serta menganalisis karakteristik marine debris yang terdampar di Pantai Sindulang. Metode penelitian yang digunakan adalah pendekatan deskriptif dengan metode survei lapangan, termasuk pengumpulan data melalui observasi, dokumentasi, dan survei langsung. Foto udara diperoleh dari drone dan pemotretan darat menggunakan kamera GPS Map serta drone. Data dianalisis menggunakan perangkat lunak Agisoft Metashape Professional dan ArcGIS 10.8 untuk memetakan sebaran titik kumpul sampah laut. Hasil pemantauan dari drone memungkinkan kita untuk mendeskripsikan karakteristik dan variasi jenis sampah laut, dengan dominasi sampah plastik diikuti oleh sampah kaca, karet, dan kain. Pesawat tanpa awak DJI Phantom 4 Pro menghasilkan foto udara dengan resolusi tinggi, yang memungkinkan identifikasi sebaran titik kumpul sampah di Pantai Sindulang serta pembuatan peta sebarannya di sepanjang pesisir laut Sindulang. Hasil pemetaan ini memberikan informasi yang berharga tentang penyebaran sampah di pantai Sindulang.  Berdasarkan hasil pemantauan menggunakan Unmanned Aerial Vehicle (UAV) / Drone, ditemukan bahwa sekitar 80% area pasang surut di pantai Sindulang telah tercakup oleh sampah, menunjukkan tingkat pencemaran yang signifikan. Kata Kunci: Marine Debris, Unmanned Aerial Vehicle, Sindulang